The Meiji Restoration as a Local Event: The Second Kiheitai in History and Memory. Issue 3 (2nd September 2018) - Hellyer, Robert
ABSTRACT: Through the story of the Second Kiheitai, a militia formed in the 1860s in the southeastern corner of the Chōshū domain (today's Yamaguchi Prefecture), this article charts a local perspective on the Meiji Restoration and its commemoration. It explores a series of tumultuous events involving the unit, created in what is today Hikari City in advance of the Tokugawa punitive expedition marshaled against Chōshū in 1866. The article also examines ways in which, influenced by the growing militarism of the age, municipal and national leaders appropriated memories of the unit in the closing days of the Pacific War. During the 1960s, some of the same leaders again commemorated the Second Kiheitai, this time as part of plans for economic expansion in the area. In addition, the article charts some of the ways that the people of Hikari today view the significance of the Second Kiheitai and, by implication, the Meiji Restoration overall, amidst an expansive, prefectural tourism campaign coinciding with the Meiji sesquicentennial.